Successful Management of Neutropenic Sepsis Is Key to Better Survival of Patients With Blood Cancer in Sri Lanka: Real-World Data From the Resource-Limited Setting - Saman Hewamana; Thurairajah Skandarajah; Chathuri Jayasinghe; Samadhi Deshapriya; Dilip Gayashan; Natasha Peiris; Mahesh Harischandra; Prasanna Gunasena; Gnani Somasundaram; Vadivelu Srinivasan; Surjit Somiah; Chandana Wickramarathna; et al. (JCO Global Oncology, 2024)
PURPOSESepsis is the main cause of nonrelapse mortality, and there are no published data on applicability of supportive care protocols from high-income countries such as Sri Lanka. The aim of the study was to investigate management and mortality of neutropenic episodes among Hemato-Oncology patients.MATERIALS AND METHODSRetrospective analysis of clinical characteristics, management, morbidity, and mortality of neutropenic Hemato-Oncology patients presented to the Lanka Hospital Blood Cancer Centre from January 1, 2019 to December 31, 2019 was performed.RESULTSA total of 169 neutropenic episodes were identified; 115 (68%) of such episodes were related to chemotherapy. Acute leukemia, lymphoproliferative disorders, and plasma cell disorders accounted for 23%, 69%, and 8% of patients, respectively. The median age of patients who had sepsis was 56 years, whereas that of those who had no sepsis was 53 years (P = .49). The median time to neutropenia was 9 days for those in the sepsis group compared with 8 days in the group that had no sepsis (0.64). The median neutrophil count in the group that had sepsis was 0.06, whereas it was 0.69 in the group that had no sepsis (P ≤ .05). The median time to commencement of antibiotics was 20 minutes.CONCLUSIONTo our knowledge, this is the only documented study related to outcome and successful applicability of western supportive care protocols to Sri Lankan patients with neutropenia. In this study, we have shown that neutropenic sepsis can be successfully managed in the setting of limited resources with service development, following guidelines and staff training.